War, genocide, and justice : Cambodian American memory work - Schlund-Vials, Cathy J., 1974- (University of Minnesota Press, 2012)
In the three years, eight months, and twenty days of the Khmer Rouge's deadly reign over Cambodia, an estimated 1.7 million Cambodians perished as a result of forced labor, execution, starvation, and disease. Despite the passage of more than thirty years, two regime shifts, and a contested U.N. intervention, only one former Khmer Rouge official has been successfully tried and sentenced for crimes against humanity in an international court of law to date. It is against this background of war, genocide, and denied justice that Cathy J. Schlund-Vials explores the work of 1.5-generation Cambodian American artists and writers. Drawing on what James Young labels "memory work"--The collected articulation of large-scale human loss--War, Genocide, and Justics investigates the remembrance work of Cambodian American cultural producers through film, memoir, and music. Schlund-Vials includes interviews with artists such as Anida Yoeu Ali, praCh Ly, Sambath Hy, and Socheata Poeuv. Alongside the enduring legacy of the Killing Fields and post-9/11 deportations of Cambodian American youth, artists potently reimagine alternative sites for memorialization, reclamation, and justice. Traversing borders, these artists generate forms of genocidal remembrance that combat amnesiac politics and revise citizenship practices in the United States and Cambodia. Engaged in politicized acts of resistance, individually produced and communally consumed, Cambodian American memory work represents a significant and previously unexamined site of Asian American critique. --